Isolation, Characterization, Kinetics, and Enzymatic and Nonenzymatic Microbicidal Activities of a Novel c-Type Lysozyme from Plasma of Schistocerca gregaria (Orthoptera: Acrididae). Issue 1 (13th May 2015) - Elmogy, Mohamed; Bassal, Taha T. M.; Yousef, Hesham A.; Dorrah, Moataza A.; Mohamed, Amr A.; Duvic, Bernard
Abstract : A protein, designated as Sg l, showing a muramidase lytic activity to the cell wall of the Gram-positive bacterium Micrococcus lysodeikticus was isolated for the first time from plasma of Escherichia coli- immunized fifth instar Schistocerca gregaria . The isolated Sg l was detected as a single protein band, on both native- and SDS-PAGE, has a molecular weight of ∼15.7 kDa and an isoelectric point (pI) of ca 9.3 and its antiserum has specifically recognized its isolated form. Fifty-nine percentage of Sg l lytic activity was recovered in the isolated fractions and yielded ca 126-fold increase in specific activity than that of the crude. The partial N-terminal amino acid sequence of the Sg l has 55 and 40% maximum identity with Bombyx mori and Gallus gallus c-type lysozymes, respectively. The antibacterial activity against the Gram-positive and the Gram-negative bacteria were comparatively stronger than that of the hen egg white lysozyme (HEWL). The detected Sg l poration to the inner membrane that reach a maximum ability after 3 h was suggested to operate as a nonenzymatic mechanism for Gram-negative bacterial cell lysis, as tested in a permease-deficient E. coli, ML-35 strain. Sg l showed a maximal muramidase activity at pH 6.2, 30–50°C, and 0.05 M Ca 2+ or Mg 2+ ; and has a Km of 0.5 μg/ml and a Vmax of 0.518 with M. lysodeikticus as a substrate. The Sg l displayed a chitinase activity against chitin with a Km of 0.93 mg/ml and a Vmax of 1.63.